2022
DOI: 10.1038/s41541-022-00432-w
|View full text |Cite
|
Sign up to set email alerts
|

Extended interval BNT162b2 vaccination enhances peak antibody generation

Abstract: The BNT162b2 vaccine is highly effective against COVID-19 infection and was delivered with a 3-week time interval in registration studies1. However, many countries extended this interval to accelerate population coverage with a single vaccine. It is not known how immune responses are influenced by delaying the second dose. We provide the assessment of immune responses in the first 14 weeks after standard or extended-interval BNT162b2 vaccination and show that delaying the second dose strongly boosts the peak a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
58
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 19 publications
14
58
2
1
Order By: Relevance
“…Humans receive a 2-dose standard regimen of mRNA-LNP vaccines at 3 to 4 weeks intervals (Walsh et al, 2020) and booster shots at different time points. Our data are strongly supported by recent studies showing that a delay of the second dose of an mRNA vaccine from 3 weeks to 3 months significantly improves the antibody response (Hall et al, 2022; Ooi and B, 2022; Parry et al, 2022). Indeed, inflammation has been related to a poor responsiveness to vaccination in earlier studies (Trzonkowski et al, 2003), and it is rational to hypothesize that the acute inflammatory side effects of the LNP platform negatively impedes induction of antibody responses during the second dose administration.…”
Section: Discussionsupporting
confidence: 89%
“…Humans receive a 2-dose standard regimen of mRNA-LNP vaccines at 3 to 4 weeks intervals (Walsh et al, 2020) and booster shots at different time points. Our data are strongly supported by recent studies showing that a delay of the second dose of an mRNA vaccine from 3 weeks to 3 months significantly improves the antibody response (Hall et al, 2022; Ooi and B, 2022; Parry et al, 2022). Indeed, inflammation has been related to a poor responsiveness to vaccination in earlier studies (Trzonkowski et al, 2003), and it is rational to hypothesize that the acute inflammatory side effects of the LNP platform negatively impedes induction of antibody responses during the second dose administration.…”
Section: Discussionsupporting
confidence: 89%
“…Since neutralizing antibodies have been shown to associate with protection against SARS‐CoV‐2 virus infection, 22 from 6 months post first dose, those with a longer dosing interval appear to have a higher level of protection. An extended dosing gap with the BNT162b2 has also been shown to increase the neutralizing antibody levels with an increase in interleukin‐2 producing CD4 + T cells 23,24 . Therefore, overall the data appear to suggest that a longer dosing interval may associate with a higher magnitude of neutralizing antibody responses.…”
Section: Discussionmentioning
confidence: 86%
“…Related studies in high-income country settings of Canada, Netherlands, the United Kingdom, and the United States also found that delaying the second dose of a two-dose COVID-19 vaccine series is beneficial. 8 , 33 , 34 , 35 Moghadas et al. used an agent-based model to compare two strategies of either vaccinating more individuals with the first dose and delaying the second dose or administering the 2-dose series according to the recommended dose spacing for Pfizer-BioNTech (BNT162b2) and Moderna (mRNA-1273) vaccines.…”
Section: Discussionmentioning
confidence: 99%